2022
DOI: 10.1101/2022.04.26.489563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trimethylamine N-oxide (TMAO) enhances substrate mechanical stability probed by single molecule magnetic tweezers

Abstract: Trimethylamine N-oxide (TMAO) is a well-known osmolyte to stabilize the folded proteins through a variety of mechanisms. Since mechanical strength of proteins is a critical determinant of its stabilization, TMAO might play a relevant role by favoring its folding dynamics or by enhancing its mechanical stability. To address this question, we have performed the single-molecule magnetic tweezers experiment to explore the TMAO effect on two structurally distinct substrates-protein L and talin. We observed that TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…• Chaudhuri et al [58]. using magnetic tweezers spectroscopy on Protein L, found that TMAO increases protein mechanical stability by increasing the the force need for unfolding, slowing unfolding and accelerating folding kinetics.…”
Section: C1 a B C2mentioning
confidence: 99%
“…• Chaudhuri et al [58]. using magnetic tweezers spectroscopy on Protein L, found that TMAO increases protein mechanical stability by increasing the the force need for unfolding, slowing unfolding and accelerating folding kinetics.…”
Section: C1 a B C2mentioning
confidence: 99%